Bronchial intraepithelial recurrence of a pulmonary large cell neuroendocrine carcinoma. (2020) - Kojima, Hideaki; Isaka, Mitsuhiro; Funai, Kazuhito; Ohde, Yasuhisa
Highlights: We describe a pulmonary LCNEC with bronchial intraepithelial recurrence. Because of its rarity, the mechanism of tumor progression of LCNEC is still unknown. Endobronchial metastases usually showed the presence of polypoid lesions. This is the first case of metastasis with bronchial intraepithelial recurrence. Clinicians should be aware of this unique recurrence type in pulmonary LCNEC. Abstract: Introduction: We encountered a case of a large cell neuroendocrine carcinoma with bronchial intraepithelial spread, a unique form of recurrence. Presentation of case: A 63-year-old man underwent middle lobectomy and systematic lymph node dissection for lung cancer. The pathological diagnosis was a large cell neuroendocrine carcinoma, and the pathological stage of the tumor was T2aN0M0, stage IB. At 30 months after surgery, the patient complained of continuous cough, and computed tomography revealed a thickened right upper bronchus. Transbronchial biopsy revealed a large cell neuroendocrine carcinoma with bronchial intraepithelial recurrence. The patient died of disease 24 months after recurrence was diagnosed. Discussion: In cases of centrally located small cell lung carcinoma, it is well known that tumor cells progress along the sub-bronchial mucosa. In contrast, the mechanism of tumor progression of large cell neuroendocrine carcinoma is not fully elucidated because of the rarity of such cases. Endobronchial metastases usually show the presence of polypoid lesions. To the best of our knowledge, this is the first case of endobronchial metastasis from a pulmonary large cell neuroendocrine carcinoma showing bronchial intraepithelial recurrence. Conclusions: Clinicians should be aware of this unique form of recurrence in patients with large cell neuroendocrine carcinoma of the lungs.